Coordination, Organizations, Institutions, Norms, and Ethics for Governance of Multi-Agent Systems XV International Workshop, COINE 2022, Virtual Event, May 9, 2022, Revised Selected Papers - Ajmeri, Nirav; Morris Martin, Andreasa; Savarimuthu, Bastin Tony Roy. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the thoroughly refereed post-conference proceedings of the International Workshop on Coordination, Organizations, Institutions, and Norms for Governance of Multi-Agent Systems, COINE 2022, which was held in Auckland, New Zealand, on May 9, 2022. The 14 papers included in these proceedings were carefully reviewed and selected from 15 submissions. They deal with autonomous agents and multi-agent systems, focusing on the scientific and technological aspects of social coordination, organizational theory, artificial (electronic) institutions, and normative and ethical MAS.
Designing International Humanitarian Law into Military Autonomous Devices -- Epistemic Diversity and Explanatory Adequacy in Distributed Information Processing -- The Complexity of Norm Synthesis and Revision -- Embracing AWKWARD! Real-Time Adjustment of Reactive Plans Using Social Norms -- Self-Learning Governance of Black-Box Multi-Agent Systems -- Computational Theory of Mind for Human-Agent Coordination -- Computational Discovery of Transaction-Based Financial Crime via Grammatical Evolution: The Case of Ponzi Schemes -- Centralized Norm Enforcement in Mixed-Motive Multiagent Reinforcement Learning -- Supporting the Reasoning about Environmental Consequences of Institutional Actions -- Social Motives and Social Contracts in Cooperative Survival Games -- Evaluating Human and Agent Task Allocators in Ad Hoc Human-Agent Teams -- Fleur: Social Values Orientation for Robust Norm Emergence -- Reasoning about Collective Action in Markov Logic: A Case Study from Classical Athens -- Design Heuristics for Ethical Online Institutions.
Keywords: Artificial intelligence; Computers, Special purpose; Computer science; Coding theory; Information theory; Artificial Intelligence; Special Purpose and Application-Based Systems; Theory of Computation; Coding and Information Theory